Limited Associations Between 5-HT Receptor Gene Polymorphisms and Treatment Response in Antidepressant Treatment-Free Patients With Depression; Frontiers in Pharmacology; Vol. 10 - Ochi T.; Vyalova N. M. Nataljya Mikhaylovna; Paderina D. Z. Diana; Pozhidaev I. V. Ivan; Loonen A. J. M.; Simutkin G. G. German Gennadjevich; Bokhan N.; Ivanova S. A. Svetlana Aleksandrovna (2019, 2019)
Title screen